Seamless vertical handover technique for vehicular ad-hoc networks using artificial bee colony-particle swarm optimisation - Abdulwahhab, Mohanad Mazin (2019)
The vehicular ad-hoc networks are becoming a significant service in recent years. However, they are facing many challenges that require solutions so that wireless communication systems are able to coexist with each other effectively. One of these challenges is the mobility solution that facilitates mobile nodes with seamless heterogeneous roaming abilities that requires a seamless handover technique. Naturally, the vertical handover that occurs during inter-system roaming requires both link layer and network layer handovers to take place once the change occurs in the network point of attachment and device interface. Many institutions and individuals are investigating and standardising efforts trying to design a final implementation of these communication layers. Nevertheless, for the particular purpose of vertical handover in a heterogeneous vehicular network, these two layers require an information preparation before any operations of handover as it affects the performance parameters directly and thus required to achieve a seamless handover. This thesis aimed to probe in detail the vertical handover in a heterogeneous vehicular ad-hoc network that comprises two significant aspects. These aspects are the information gathering of the network and the information usage during the vertical handover. Firstly, we proposed a multi-criteria artificial bee colony hybrid with particle swarm optimisation algorithm (MC ABC-PSO) for evaluating the information gathered from the mobile nodes in the handover. The algorithm will process and calculate the required handover timing for each node in advance, based on the mobile nodes’ velocity and received signal strength to reduce the handover process latency. Secondly, the information is used to support all vertical handover operations, which includes network discovery, handover decision, and handover implementation. In the initial stage of the operation, the previous access point provides information about the neighbouring networks for the mobile node (MN) to quickly discover available networks. The second stage of the operation is selecting the best available network for the MN by considering its velocity and distance. The final operation involves the mobile node sharing the current information with its neighbours’ nodes based on its current location. The results show the benefits of the proposed MC ABC-PSO method by reducing the handover decision delays by 25%. It gives the optimum performance in terms of network selections and reducing the handover latency by 14.5% and the number of unnecessary handovers by 48% as compared to the previous technique for three different mobility scenarios based on traffic environments (highway, urban and traffic jam).